Incorporating unsaturated shear strength function in slope stability analysis San Jose, Antipolo case study - Alcantara, Matthew Travis M.
Slope stability analysis generally uses the saturated shear strength of soils as basis for computations of factor of safety. The soil suction introduced by unsaturated soils was incorporated in the slope stability analysis for this study. A site surrounding Cabading Elementary School, Antipolo, Rizal was analyzed in this study. The rainfall event during the Habagat last August 2013 was simulated for transient seepage as triggering factor. Generalized limit equilibrium (GLE) method was employed to analyze circular slip surfaces. All computations used the software Slide 6.0 by Rocscience to perform seepage groundwater conditions and slope stability analysis by fInite elements. The parametric study observed that the internal angle of friction and the unsaturated shear strength angle have the most influence in the factor of safety. The dry unit weight of the soil has an inverse relationship with factor of safety. Moreover, unsaturated shear strength provide great effect in the stabilization of slopes for initially dry soils. For slopes with a high initial water table, the factors of safety with unsaturated strength incorporated approach those that considers saturated strength only.